How to Avoid an Upside-Down Orientation of the Graft during Descemet Membrane Endothelial Keratoplasty?. (4th August 2019) - Wasielica-Poslednik, Joanna; Schuster, Alexander K.; Rauch, Lilian; Glaner, Jessica; Musayeva, Aytan; Riedl, Jana C.; Pfeiffer, Norbert; Gericke, Adrian
Abstract : Purpose . Incorrect anterior-posterior orientation of the Descemet endothelial complex (DEC) is one of the causes of failure of Descemet membrane endothelial keratoplasty (DMEK). We evaluated a new marking technique to avoid such a misorientation. Method . A new marking technique of the DEC was evaluated in patients requiring primary DMEK. A Braille-"R"-letter was applied dot by dot onto the stromal surface of the DEC after lifting it by injecting an air-bubble into the interface between the endothelial surface of the partially stripped graft. The positioning of the graft was intraoperatively controlled by an orientation of the Braille-"R"-letter. Laboratory tests were conducted to test the impact of the marking technique on endothelial cell count. Results . We included prospectively 37 eyes of 30 patients. Four eyes were phakic and 33 pseudophakic. Five grafts (14%) presented an undifferentiated rolling tendency in the anterior chamber, and evaluation of their positioning was possible due to orientation of the mark alone. In case of an upside-down orientation, grafts were flipped immediately. A correct orientation of the graft was achieved in all cases at the end of the surgery. The endothelial cell loss due to the mark was estimated to be less than 0.3%. At 3- and 6-month follow-ups, the mean best-corrected visual acuity was 0.21 ± 0.15 and 0.15 ± 0.11 logMAR, respectively, and endothelial cell density was 1661 ± 349 and 1618 ± 396 cells/mm 2, respectively. Only one patient (3%) needed re-bubbling. Conclusions . To rely on the natural rolling tendency of the graft alone does not assure its correct positioning in all cases. Creation of the mark with 4 dots punctuated on the air-lifted stromal side of the DEC is a simple and endothelial cell saving marking method to ensure correct orientation of the graft during DMEK.